ANALYSIS OF LANDSLIDE CAUSES IN NANGGERANG VILLAGE, SUKASARI SUB DISTRICT, SUMEDANG REGENCY THROUGH IDENTIFICATION LANDSLIDE SLOPE MATERIAL CHARACTERISTICS - Aruan, Immanuel Hareanto; Yuniardi, Yuyun; Khoirullah, Nur; Sophian, Raden Irvan (Journal of Geological Sciences and Applied Geology, 2024)
On February 3, 2024, a landslide occurred in Nanggerang Village, Sukasari District, Sumedang Regency, West Java Province. The landslide took place on the slopes of local farmland. This event was investigated through an analysis of the characteristics of the landslide material collected immediately after the landslide to determine its cause and mechanism. The landslide slope was divided into three units based on the type and degree of weathering: topsoil (OH), silt soil (MH), and weathered tuff rock. Three undisturbed samples were used in laboratory experiment to determine the materials’ physical characteristics. The physical characteristics of the two soil units, which included silt-sized grains, a specific gravity of roughly 2.6, a unit weight ranging from 21 to 45 kN/m3, and a plasticity index of 16 to 20, were not substantially different, according to the results of the laboratory tests. For the tuff rock, the unit weight was 17.31, water content 48.8, and specific gravity 22.7. The laboratory test results, and studio analysis found that the high water content in the soil due to rainfall caused the two soil units to exceed their liquid limit, resulting in a translational (arc) landslide. The presence of clay minerals due to weathering acted as a catalyst for the landslide. The addition of water from heavy rainfall made the material more fluid, changing the type of landslide to an earth flow.